The Relationship Between Motivation And Application Of Therapeutic Communication By Nursing Students Of Stikes Medistra Indonesia In 2022 - Ghaziah, Siti; Simamora, Rotua Suriany; Bunga, Dinda Nur Fajri Hidayanti (Rena Cipta Mandiri, 2023)
Motivation is an impulse from within students to improve their performance and fulfill their needs. One of the basic nursing skills that must be mastered by nursing students is therapeutic communication. Therapeutic communication is a consciously planned communication with its goals and activities focused on healing the patient. There are still many nursing students in taking action the nurse does not introduce themselves first, when measuring vital signs the nurse does not ask the patient's identity first, in administering medication the nurse does not explain what drug will be given to the patient, unless the patient asks. This study aims to determine the relationship between motivation and the application of therapeutic communication by nursing students at STIKes Medistra Indonesia in 2022. The research used is quantitative with cross sectional. The population is 8th semester nursing students of STIKes Medistra Indonesia in 2022 totaling 131 students. Data collection technique using simple random sampling. It was found that with a significant level of 95% or a value of 5% (0.05) the p value (0.004) < value (0.05). There is a Relationship between Motivation and Application of Therapeutic Communication by Nursing Students of STIKes Medistra Indonesia in 2022. There is a Relationship between Motivation and Application of Therapeutic Communication by Nursing Students of STIKes Medistra Indonesia in 2022. Therapeutic communication, motivation and application of therapeutic communication.